The value of multimodal MRI in the clinical grading of acute cerebral infarction - Gui, Haiyan; Zhang, Jingjing; Lian, Jianxiu; Yang, Ningdi; Li, Hongwei (Frontiers in Neuroscience, 2025)
IntroductionAcute ischemic stroke (AIS) is one of the prevalent types of stroke, characterized by high mortality and disability rates. For reperfusion therapy in acute cerebral infarction, early and accurate identification of ischemic penumbra, collateral circulation, and clinical grading is crucial for clinicians in devising effective treatment strategies and assessing prognosis.MethodsPatients diagnosed with AIS were prospectively examined. In this study, the patients were divided into two groups based on National Institutes of Health Stroke Scale score, including the severe (score ≥ 6, 36 patients) and mild (score < 6, 51 patients) groups. Quantitative analysis included diffusion-weighted imaging (DWI) diffusion restricted maximum area, three-dimensional arterial spin labeling (3D-ASL) low-perfusion zone maximum area, and 3D-ASL cerebral blood flow (CBF) values. For qualitative analysis, four-dimensional triggered angiography non-contrast enhanced (4D-TRANCE) was used to assess hemodynamics features with a 4-point grading system. Differences among multiple groups were evaluated by analysis of variance. Receiver operating characteristic (ROC) curves were generated to assess the predictive ability.ResultsThe severe group had 21 males and 15 females, while there were 27 males and 24 females in the mild group, with no statistically significant differences in age (64 ± 12 versus 63 ± 12 years, P > 0.05). Statistical differences were found between these two groups in 3D-ASL low-perfusion zone maximum area and 4D-TRANCE grade (P < 0.001). The area under the curve of the combined model of these two parameters was 0.950, with a sensitivity of 88.9% and a specificity of 92.2%.ConclusionThe combined application of 3D-ASL and 4D-TRANCE is of predictive significance in the clinical grading of acute ischemic cerebral infarction. It could provide a multiparametric and objective basis for further diagnosis and treatment selection.